Estudo sistematico das propriedades termodinâmicas e criticalidade de filmes finos e super-redes magnéticas - Cabral Neto, João dos Santos (2004)
In this work we will study through the differential operator technique the surface effect in anisotropic spin ½ quantum Heisenberg model, through theory of effective field (EFT), of a two-spins cluster, in case of simple cubic lattice. Those systems are characterized by the existence of the surfaces, thin films and superlattice, or the bulk. Therefore, the exchange interaction, among the nearest-neighboring, depends on the position of the atoms in the lattice: with the existence of surfaces we have for atoms in those plans, exchange interactions Js and in the adjacent plans interaction J. We studied the thermodynamic properties of the quantum metamagnet for the simple cubic lattice. The limit of stability of the phase antiferromagnetic is presented for the ground state (T = 0) and the respective diagrams of phases are analyzed. With the choice of the interlayer coupling interaction different from the existent in the plane (interplane), parameter λ (interaction λJ), we analyzed the influence of the crossover in the dimensionality [2d(λ =10-5) → 3d(λ =1.0)] of the system in the thermodynamic properties with the appearance of an anomaly in magnetic susceptibility. The surface effect in the thermodynamic properties is treated taking the system on thickness film l, with exchange interactions F and AF, where in that last one we applied an external field. We observed the behavior of the thin film in function of the temperature, number of layers, magnetic field and the ratio Js/J. Changing the exchange interaction between the elements and the layers of the thin film, we characterized the system as a magnetic superlattice. We chose four arrangements in the construction of the superlattice: different inter and interlayer ferromagnetic (F) interaction, the same for antiferromagnetic (AF), alternating the layers among F, and alternating superlattice composed of F (with l1 layers) and AF (with l2 layers), where l = l1 + l2 is the thickness of the film, where we observed the influence of the change of the exchange interaction in the thermodynamic properties and in the critical properties. Several phenomena were observed, as for instance, oscillation in the magnetizations and susceptibility for layers in certain values of the temperature and coupling parameters.